IC 8284 Water Use In The Petroleum And Natural Gas Industries (eeba5f52-0cbc-4684-a58c-f2887b4eaf41) - Paul M. Buttermore (The National Institute for Occupational Safety and Health (NIOSH), 1966)
As part of a national canvass of water use the Bureau of Mines compiled data on water requirements in the petroleum and natural gas industries for the calendar year 1962, specifically in well drilling, secondary-recovery operations, and natural gas processing plants. Total new water use in the petroleum industry of the United States, excluding refining, was 5.3 billion barrels. Secondary-recovery operations and natural gas processing plants required about 2.5 billion barrels of new water input; each of these requirements was about eight times greater than that for well drilling. Total use, including recirculated water, was 45.3 billion barrels of which 3.4 billion barrels was consumed. The greatest use of recirculated water was for natural gas processing, amounting to 38.2 billion barrels. Projections of total water use show that by 1975, 75.4 billion barrels will be used by the petroleum industry, of which 10.2 billion barrels will be new water. By 1985, the total use requirement will be 92.8 billion barrels, of which 13.1 billion barrels will be new water.